Integrating Free Open Source Hardware as Educational Tool to Investigate the RLC Circuit Time Response - Serrano-Pérez, E. (Revista Cubana de Física, 2018)
In this work the experimental identification to a step response of a series RLC circuit is presented using Arduino open source software and hardware. The low cost for developing the experimental setup makes it attractive to be implemented as an educational tool in the analysis of electric circuits. A comparison between experimental results using the Arduino board and a mathematical modeling implemented in SCILAB is presented.